Characterizing the effect of incrementally increasing dry bulb temperature on linear and nonlinear measures of heart rate variability in nonpregnant, mid-gestation, and late-gestation sows. (10th January 2022) - Byrd, Christopher J; McConn, Betty R; Gaskill, Brianna N; Schinckel, Allan P; Green-Miller, Angela R; Lay, Donald C; Johnson, Jay S
Abstract: Characterizing the sow physiological response to an increased heat load is essential for effective heat stress mitigation. The study objective was to characterize the effects of a 400-min heating episode on sow heart rate variability (HRV) at different reproductive stages. HRV is a commonly used noninvasive proxy measure of autonomic function. Twenty-seven sows were enrolled in the study according to their gestation stage at time of selection: 1) nonpregnant (NP; n = 7), 2) mid-gestation (MID; 57.3 ± 11.8 d gestation; n = 11), and 3) late-gestation (LATE; 98.8 ± 4.9 d gestation; n = 8). The HRV data utilized in the study were collected from each pig as the dry bulb temperature in the room increased incrementally from 19.84 ± 2.15 °C to 35.54 ± 0.43 °C (range: 17.1–37.5 °C) over a 400-min period. After data collection, one 5-min set of continuous heart rate data were identified per pig for each of nine temperature intervals (19–20.99, 21–22.99, 23–24.99, 25–26.99, 27–28.99, 29–30.99, 31–32.99, 33–34.99, and 35–36.99 °C). Mean inter-beat interval length (RR), standard deviation of r-r intervals (SDNN), root mean square of successive differences (RMSSD), high frequency spectral power (HF), sample entropy (SampEn), short-term detrended fluctuation analysis (DFAα1 ), and three measures (%REC, DET, LMEAN) derived from recurrence quantification analysis were calculated for each data set. All data were analyzed using the PROC GLIMMIX procedure in SAS 9.4. Overall, LATE sows exhibited lower RR than NP sows ( P < 0.01). The standard deviation of r–r intervals and RMSSD differed between each group ( P < 0.01), with LATE sows exhibiting the lowest SDNN and RMSSD and NP sows exhibiting the greatest SDNN and RMSSD. Late-gestation sows exhibited lower HF than both MID and NP sows ( P < 0.0001), greater DFA values than NP sows ( P = 0.05), and greater DET compared to MID sows ( P = 0.001). Late-gestation also sows exhibited greater %REC and LMEAN compared to MID ( P < 0.01) and NP sows (all P < 0.01). In conclusion, LATE sows exhibited indicators of greater autonomic stress throughout the heating period compared to MID and NP sows. However, temperature by treatment interactions were not detected as dry bulb increased. Future studies are needed to fully elucidate the effect of gestational stage and increasing dry bulb temperature on sow HRV. Lay Summary: Pregnant pigs may be at a higher risk of poor physiological outcomes due to heat exposure compared to mature female pigs that are not pregnant. The purpose of this study was to evaluate the stress response of pregnant pigs to increasing environmental temperatures using heart rate variability, a noninvasive measure commonly used to evaluate the physiological stress response. Our findings show that pregnant pigs, particularly those who are closer to giving birth, exhibit greater evidence of physiological stress compared to pigs who are not pregnant. However, we did not find evidence that increasing environmental temperature throughout the experimental period was a primary reason for the increased stress exhibited by pregnant pigs. It is possible that the physiological changes that normally occur during pregnancy may have masked the physiological stress response typically associated with increased heat exposure. Abstract : Sow heart rate variability is affected by advancing gestation, not dry bulb temperature, during a period of gradually increasing environmental temperature.